ANALISIS GUGATAN UNI EROPA DI WTO TERHADAP INDUSTRI KELAPA SAWIT INDONESIA - Sulistya, Neva Agsa (Universitas Muhammadiyah Tapanuli Selatan, 2023)
impact of the European Union's lawsuit at the WTO on the Indonesian palm oil industry and provide recommendations to improve the sustainability of the Indonesian palm oil industry. It was found that this lawsuit could create legal uncertainty, encourage Indonesia to increase the sustainability of the palm oil industry, as well as affect the selling price and demand for Indonesian palm oil products. Efforts need to be made to increase the sustainability of the Indonesian palm oil industry and to diversify exports. The Indonesian palm oil industry needs to continue to develop in a sustainable manner and make a significant contribution to the country's economic growth.Keywords: Anti-Dumping, Export Diversification, WTO Lawsuit, Palm Oil, European Union.